Green Rural Infrastructure and Economic Recession, Research in China, USA and Europe, also Potential Future Research in Indonesia - Muhammad Ikhsan Setiawan; Agus Sukoco; Dahlan Abdullah; Cut Ita Erliana; Paisal Halim; Syamsiah Badruddin; Hery Budiyanto (LPPM of NAROTAMA UNIVERSITY, 2022)
The impact of rural land utilization, which further affects the spatial structure and efficiency of rural ecosystems. With recession, the spatial distribution of dwelling values was more heterogeneous and decoupled from the socioeconomic profile of local contexts, with the highest growth rate recorded in accessible rural districts and coastal areas - including islands. Documents by years by country or territory, compare the document counts for up to 15 countries/territories, USA, UK, China, Italy and India are very dominant in the World. In ASIA Indonesia 3rd rank and in ASEAN 1th rank for Green Rural Infrastructure documents result since 2000 to 2021 SCOPUS.COM research publication. This is excellent for Green Rural Infrastructure development in Indonesia. But for Rural Economic Recession documents result since 2000 to 2021, there are no Indonesia documents research publication. So for this, challenge for Indonesia. The best 3 journals are well established, with good editor and good article. None by source, from Indonesia, documents per year by source. Indonesia only 1(one) by funding sponsor, Lembaga Penelitian dan Pengabdian. Indonesia better support more funding sponsor for Green Rural Infrastructure and Rural Economic Recession. Indonesia, totally 270,277 document SCOPUS.COM since 1849, dominant documents by subject area, Engineering, followed by Environmental Science and Physics and Astronomy. So this is connected between Indonesia research publication by subject area trend and world trend in Green Rural Infrastructure and Rural Economic Recession. Indonesia only 1(one) affiliation with Universitas Diponegoro, Semarang, in SCOPUS.COM from 1986 to 2023 have 2,082 documents, dominant subject area with Environmental Science, Earth and Planetary Sciences, Engineering, Agricultural and Biological Sciences, and Medicine. So there are connection between Green Rural Infrastructure, Rural Economic Recession, and research trend in Universitas Diponegoro, Semarang, Indonesia.